Millennial-scale variability during the last glacial in vegetation records from Europe - Fletcher, William J.; Sánchez Goñi, Maria Fernanda; Allen, Judy R. M.; Cheddadi, Rachid; Combourieu-Nebout, Nathalie; Huntley, Brian; Lawson, Ian; Londeix, Laurent; Magri, Donatella; Margari, Vasiliki; Müller, Ulrich C.; Naughton, Filipa; et al. (Quaternary Science Reviews, 2010)

Orbital- and sub-orbital-scale climate impacts on vegetation of the western Mediterranean basin over the last 48,000 yr - Fletcher, William J.; Sánchez Goñi, Maria Fernanda (Quaternary Research, 2008)
High-resolution pollen analysis of Alborán Sea core MD95-2043 provides a 48-ka continuous vegetation record that can be directly correlated with sea surface and deep-water changes. The reliability of this record is supported by comparison with that of Padul (Sierra Nevada, Spain). Marine Isotope Stage (MIS) 3 was characterised by ﬂuctuations in Quercus forest cover in response to Dansgaard-Oeschger climate variability. MIS 2 was characterised by the dominance of semi-desert vegetation. Despite overall dry and cold conditions during MIS 2, Heinrich events (HEs) 2 and 1 were distinguished from the last glacial maximum by more intensely arid conditions. Taxon-speciﬁc vegetation responses to a tripartite climatic structure within the HEs are observed. In MIS 1, the Bölling-Allerød was marked by rapid afforestation, while a re-expansion of semidesert environments occurred during the Younger Dryas. The maximum development of mixed Quercus forest occurred between 11.7 and 5.4 cal ka BP, with forest decline since 5.4 cal ka BP. On orbital timescales, a long-term expansion of semi-desert vegetation from MIS 3 into MIS 2 reﬂects global ice-volume trends, while Holocene arboreal decline reﬂects summer insolation decrease. The inﬂuence of precession on the amplitude of forest development and vegetation composition is also detected
The following values have no corresponding Zotero field: publisher: University of Washington
Keywords: Dansgaard-Oeschger variability; Heinrich events; Holocene; Iberian margin; Land–sea correlation; LGM; Marine palynology; Mediterranean Region; Precession